Predictors of major adverse events after stent implantation for atherosclerotic renal artery stenosis - Koca, Fatih; Demir, Ömer Furkan (The European Research Journal, 2025)
Objectives: Atherosclerotic renal artery stenosis (ARAS) is the most frequently seen cause of secondary hypertension (HT). ARAS associated with adverse cardiovascular events independently of other traditional cardiovascular risk factors, and increased mortality. Percutaneous transluminal renal arterial stenting (PTRS) is important methods in ARAS treatment. The aim of this study was to investigate major adverse events (MAE) and potential predictors in patients undergoing PTRS for ARAS by evaluating variables before and immediately after the procedure, including the SYNTAX score. Methods: One hundred and five consecutive patients who underwent PTRS over a period of approximately 10 years were included in our study. Patients were divided into two groups, MAE negative (-) and MAE positive (+), according to the occurrence of MAE. After comparing both groups with difference tests, independent predictors were investigated with univariate and multivariate Cox regression analysis. Afterwards, Receiver Operating Characteristics (ROC) analysis was performed on independent predictors. Results: The average age of the patients was 63.32±11.62 years (range: 30-83 years) and 52 (49.5%) of them were male. Sixty-two patients constituted the MAE (-) and 43 the MAE (+) groups. In multivariate Cox regression analysis, chronic obstructive pulmonary disease (COPD), left ventricular ejection fraction (LVEF), and the total number of antihypertensives after the procedure were identified as independent predictors. As a result of the ROC analysis, a cutoff value of ≤55% for LVEF was determined to have area under the curve (AUC) 0.733, 69.8% sensitivity, and 77.42% specificity (P